Efektivitas Model Pembelajaran Controversial Public Issues dalam Meningkatkan Critical Thinking Skills Peserta Didik Kelas XI IPS pada Mata Pelajaran Ekonomi - Dhita Aulia Rahmayanti; Syahrul Munir (Jurnal Pendidikan Ekonomi, 2023)
Research aims to find out how the controversial public issues model in improving the critical thinking skills of students in achieving the dimensions in Pancasil Student Proful in XI class economics subjects. Impure experiments were used in this research, with XI IPS 2 class subjects as experimental classes and XI IPS 5 as control classes. The data collection technique consists of a five - page pretest and post writing test. The Independent Sample T-test for N-Gain score was selected for data analysis techniques. The results of the Independent Sample T-test for N-Gain scor showed that the average critical thinking skill score of students using the controversial public issues model was higher at 72.14 or was in the category quite effective compared to students using discovery learning strategies of 36.26 or fall into ineffective categories. That is, the public issues controversial learning model is effective enough to help improve critical thinking skills, the application of this learning model has better results than the discovery learning model in the control class. In the Independent Sample-Test for N-Gain score test, a significance level of 0.000 < 0.05 (significant value), H0 was rejected, which meant that there was an influence of the controversial public issues model on students critical thinking skills in the economics subjects of class XI IPS.So, implementation of a public issues controversial learning model can improve the critical thinking skills dimensions contained in the Profil Pelajar Pancasila in economics subjects. That is, public issues controversial learning models can increase the dimension of critical thinking skills through honing the ability of analysis, evaluation, explanation, inference, and evaluation. and interpretations that will be integrated into learning activities on public issues in the field of economics so that they can reach the dimensions contained in the Profil Pelajar Pancasila as a transition to implementing the Kurikulum Merdeka.